Prevalence of Social Isolation Among Older Adults in Tehran, Iran, and Its Associated Factors - Niloufar Mahmoudi; Yadollah Abolfathi Momtaz; Mahshid Foroughan; Nasibe Zanjari; Seyyed H Mohaqeqi Kamal (University of Social Welfare and Rehabilitation Sciences, 2022)
Objective: Social isolation is one of the important concerns in the elderly population which can negatively affect their quality of life and health. The present study aims to determine the prevalence of social isolation among older adults aged 60 years and older in Tehran, Iran and find its associated factors. Materials & Methods: This is a secondary analysis study on data obtained from a large cross-sectional study conducted on older adults in Tehran in 2020. The Persian version of lubben social network scale (LSNS-6) was used to measure social isolation. The demographic characteristics (age, gender, marital status, living arrangements, and number of children), socio-economic status (educational level, employment status, and household income) and health-related information (history of chronic diseases and use of assistive devices) were collected using a checklist. Data were analyzed in SPSS v. 23 software using multivariate logistic regression analysis. The significance level was set at Results: The data were related to 1280 older adults aged 60 years and older (Mean±SD age=70.97±8.07 years). The prevalence of social isolation was 30.8%. The results of chi-square test revealed that living arrangement (P<0.001, X2=46.93), marital status (P<0.001, X2=26.91), household income (P<0.001, X2=67.44), level of education (P<0.05, X2=20.26), employment status (P <0.001, X2=29.21), musculoskeletal problems (P<0.001, X2=15.47), respiratory problems (P<0.05, X2=10.43), vision problems (P<0.05, X2=4.4), hyperlipidemia (P<0.001, X2=13.53), and wearing glasses (P<0.05, X2=3.92) had significant association with social isolation. The regression analysis model could significantly predict social isolation (X2=188.35, P<0.001). The model revealed that being male (P<0.05, OR=1.7), living with spouse (P<0.05, OR=0.4), musculoskeletal disease (P<0.05, OR=1.42), diabetes (P<0.05, OR=1.41), household income (P<0.001, OR=5.82), being unemployed (P<0.001, OR=2.13), having hyperlipidemia (P<0.001, OR=0.58), and living in developed areas (P<0.001, OR=2.02) significantly predicted the social isolation. Conclusion: There is a strong association between social isolation and some socio-economic, demographic-health related factors in older adults. Health policymakers and healthcare experts can develop the screening and prevention programs related to the mental and social health of older adults in Tehran, Iran in order to moderate and control these factors.